Evaluation of Alternative Culling Strategies for Maintenance of Genetic Variaton in Bison (Bison Bison) - (:unkn) unknown (My University, 2014)
Bison (Bison bison) once numbered in the millions and roamed across much of the lower 48 states. By the late 1800s, overhunting had reduced the population to around 1,000 individuals. Strong efforts to establish managed herds have resulted in a steady bison population increase. Currently, six herds are maintained by the U.S. Fish and Wildlife Service (FWS) at National Wildlife Refuges (NWRs) and are intensively managed through annual culling to keep herd size at targeted levels. Although various criteria have historically been used to select individuals for culling, the FWS currently employs an allele frequency based strategy that we have generalized as the mean allele frequency (MAF) strategy, with the goal of keeping at least a few individuals that represent each element of genetic variation. Other bison management entities such as the National Park Service often use random culling or slight variations thereof. We have developed an individual-based model to compare the MAF and the random removal of young culling strategies to a proposed pedigree-based strategy based on the field of zoo biology to cull individuals based on kinship. The model was parameterized using existing long-term demographic and genetic data from the herd located in the Fort Niobrara NWR, Nebraska. Models were run at 100, 200, and 500 year marks. Variation among iterations was greatest within the random removal of young culling strategy. This model was outperformed by the pedigree-based and MAF culling strategies across summary statistics (allelic richness, gene diversity, inbreeding, and heterozygosity). A trade off was observed between the pedigree-based strategy and the MAF culling strategies in that the MAF culling strategy performed the best in regards to retaining the highest allelic richness (A) and observed heterozygosity (H) and the pedigree-based culling strategy retained the most gene diversity (GD) and maintained the lowest amount of inbreeding (F) . The models will aid in the long-term management of bison and provides a useful tool for other intensively managed mammal species.
Keywords: Bison; Culling Strategies; Genetic Variation; Inbreeding; Population Management